Penerapan Scrum Pada Perancangan Sistem Informasi Rumah Santri Indonesia - Reni Widyastuti; Tri Hartati; Budi Supriyadi (Justek : Jurnal Sains dan Teknologi, 2024)
Abstract:  The santri house was founded on September 13 2017 by the Indonesian Santri House Foundation located in Central Jakarta. The implementation of services provided to the community and especially prospective students who are accepted either through the scholarship route or the independent route is still carried out manually, resulting in obstacles in the development of new student registration services. This research aims at the Rumah Santri Indonesia Foundation to improve manual services to become computerized so that an integrated information system can be built so that it can improve excellent services. The method for developing a student service information system uses a Scrum frame in agile development with a systematically structured framework so that the implementation of the information system development is shorter. As a result, this santri registration service system has maximum performance so that all parties with an interest in the Santri House are served and can provide increased trust in the Foundation.Abstrak: Rumah santri didirikan sejak tahun 13 September 2017 oleh Yayasan Rumah Santri Indonesia berlokasi di  Jakarta Pusat. Pelaksanaan layanan yang diberikan ke masyarakat dan khususnya para calon santri yang diterima baik dengan jalur bea siswa atau jalur mandiri masih dilakukan manual sehingga terjadi hambatan dalam pengembangan layanan pendaftaran santri baru. Penelitian ini bertujuan Yayasan Rumah Santri Indonesia memperbaiki pelayanan manual menjadi terkompeterisasi sehingga dibangun sistem informasi yang terintegrasi sehingga dapat meningkatkan layangan prima. Metode pembangunan sistem informasi layanan santri dengan menggunakan Frame Scrum pada Agile Devolepment dengan kerangka kerja yang tersusun sistematis  sehingga pelaksanaannya pembangunan system informasi lebih singkat. Hasilnya sisitem layanan pendaftaran santri ini memiliki  performa yang maksimal sehingga seluruh pihak yang berkepentingan dengan Rumah Santri terlayani dan dapat memberikan peningkatan kepercayaan pada Yayasan.